“Da conjuração dos versos”: a expressão poética feminina afro-brasileira de Conceição Evaristo - Oliveira, Joilda Alves de (2021)
Conceição Evaristo's literary production is becoming more commented on in academic environments, whether in dissertations, theses, or scientific articles. His works are becoming better known and are recurrent objects of research in the field of Literary Studies. The expansion of the scope of his creations constitutes an advance for the consolidation of the place of existence and speech of works of female authorship in contemporary Brazilian literature. This work uses Poems of Remembrance and other movements as the object of research, in order to analyze the Afro-Brazilian female figure expressed through contemporary Brazilian poetry of female authorship. We intend to establish a dialogue between the aesthetic and social issues that permeate Conceição Evaristo's poetics. In the work in question, the marks of contemporary poetry will be identified. In addition to observing the female image of the black woman that is constituted through the author's poetics. The analysis of poems will focus on reading the procedures of language, metaphorization, rhythm and, in some cases, prosaism; because these resources are intertwined with themes related to memory, engagement and female figuration. Aspects such as: the correlation between Evaristo's work and contemporary poetics will be highlighted; the singularization of the “feminine” in Evaristo; and the approach of aspects of relevance to the understanding of lyricism and memory, in addition to intertextual procedures and the possible dialogue between lyricism and social context. Throughout the work, poems are present that dialogue with prominent themes within the Afro-Brazilian female universe such as oppression, abortion, the social role of women, discrimination, the presence of women in literature, among others. The engagement of the black woman is notable, which puts into debate the oppressions suffered by her class in the most diverse spheres. For the research work, some poems from the collection will be highlighted, which has sixty-six poems. The theoretical approaches that make up the research seek a dialogue between the studies of criticism and literary theory, theories about the textual genre poem, contemporary Brazilian poetry and some conceptions of Cultural Studies. Among the theorists used are: Staiger (1997), with a study on the lyrical genre; Rezende (2014), which brings concepts about contemporary Brazilian poetry; Duarte and Lopes (2020), scholars of the works of C. Evaristo; Álos (2011), with criticism referring to the work of Evaristo; and Bordini (2009), who reflects on Cultural Studies. Regarding the analysis of the image of the black woman in the poems, the studies by Ribeiro (2017), which presents reflections related to the place of speech directed to Afro-Brazilian women, and Evaristo (2009) with their analytical view of black literature, will be used. The analysis of the literary corpus will seek to reflect, in the light of the relevant theories, on the image of Afro-Brazilian women expressed through poems. Therefore, an attempt is made to analyze the aesthetic issues present in the texts and their relationship with the Afro-Brazilian female figure, a process of analysis that raises questions of a socio-cultural nature.